ANALISIS PENGARUH KARAKTERISTIK INDIVIDU TERHADAP KINERJA PEGAWAI MELALUI INTERPRENEURSHIP SEBAGAI VARIABEL MEDIASI DI UMKM - Husien, Nirza Marzuki (Fakultas Ekonomi Universitas IBA, 2019)
The attention of the public and the government and the world of education towards small business communities in the form of small and medium micro enterprises (MSMEs) is currently quite large considering the large number of jobs created from this business. But the development of uneven MSMEs is still small, especially from the financial aspect. Much assistance has been given both from soft loans and other business facilities as well as various trainings. This study attempts to examine the effectiveness of individual characteristics of employee performance through the employee's interpreneur spirit. This research was conducted on 133 usha practitioners both as owners, owners and perpetrators, as well as employees of MSMEs in the forestry sector such as making furniture, transporting timber, and providing building materials from wood. The results of the study show that the interpreneur spirit of employees successfully mediates the influence of individual characteristics to improve the performance of MSME employees. So that it is expected that MSME managers must select employees to consider the spirit of their interpreneur and include their employees in entrepreneurship training.